Isolation of Sarcolemmal Plasma Membranes by Mechanically Skinning Rat Skeletal Muscle Fibers for Phospholipid Analysis. Issue 4 (22nd February 2013) - Fajardo, Val Andrew; McMeekin, Lauren; Basic, Admir; Lamb, Graham D.; Murphy, Robyn M.; LeBlanc, Paul J.
Abstract: Membrane phospholipid (PL) composition has been shown to affect cellular function by altering membrane physical structure. The sarcolemma plasma membrane (SLpm ) is integral to skeletal muscle function and health. Previous studies assessing SLpm PL composition have demonstrated contamination from transverse (t)‐tubule, sarcoplasmic reticulum, and nuclear membranes. This study assessed the possibility of isolating SL by mechanically skinning skeletal muscle fiber segments for the analysis of SLpm PL composition. Mechanically skinned SLpm from rat extensor digitorum longus (EDL) muscle fibers underwent Western blot analysis to assess contamination from t‐tubule, sarcoplasmic reticulum, nuclear and mitochondrial membranes. The results indicate that isolated SLpm had minimal nuclear and mitochondrial membrane contamination and was void of contamination from sarcoplasmic reticulum and t‐tubule membranes. After performing both high‐performance thin layer chromatography and gas chromatography, we found that the SLpm obtained by mechanical skinning had higher sphingomyelin and total fatty acid saturation and lower phosphatidylcholine when compared to previous literature. Thus, by avoiding the use of various chemical treatments and membrane fractionation, we present data that may truly represent the SLpm and future studies can use this technique to assess potential changes under various perturbations and disease conditions such as insulin resistance and muscular dystrophy.